Digitalization of People’s Daily Routine in the 21st Century - Parijkova, Lubomira; Mitkova, Yanislava; Lyubenov, Stanislav (Bobcatsss, 2023)
Through the ages of time, mankind has always been in a constant motion towards revolutionization – abandoning old habits and paving new paths for the next generations so they could live a better and more easeful life, was and always will be number one priority of our ancestors. Digital Revolution began in late 20th century and we are still living in it though it is nearing the end of its lifespan. Another problem for our society is that digitalization is perceived in different ways by generations such as Х, У, Z, Alpha. The focus of our research is the ongoing processes that are directly or indirectly connected with the Digitalization as a new historic period such as critical digital literacy, development of new artificial intelligence, the digitalization of our personal lives – a threat to our privacy or a new frontier aimed at getting people together, the future professions. This study also presents some results from our survey conducted with parents towards their children’s habits with digital technologies.